A new capacitive displacement sensor with high accuracy and long-range - Kim, Moojin; Moon, Wonkyu; Yoon, Euisung; Lee, Kwang-Ryeol (ELSEVIER SCIENCE SA, 2006)
A new capacitive displacement sensor is designed and fabricated for measurement of a large displacement with very high accuracy. This sensor is a kind of linear encoder with an array of microelectrodes made by micromachining processes. The two patterned electrodes on the sensor substrates are assembled facing each other after being coated with thin dielectric film. Due to the resulting small gap size, it is highly sensitive to displacement but minimizes expected misalignments such as tilting error. The sensor fabricated as a sample has a grating of electrodes with a width of 20 mu m which is coated with a diamond-like carbon (DLC) film 0.4 mu m thick. The proposed sensor was tested to conclude that its resolution is 0.9 nm for the measuring range of 15 mm and that the linearity error is expected to be less than 0.0026% of the measurable range. (c) 2005 Elsevier B.V. All rights reserved.